ANALISIS EFEKTIVITAS PROGRAM BANPRES PRODUKTIF USAHA MIKRO (BPUM) BAGI KELANGSUNGAN USAHA DI TENGAH PANDEMI - S Suprianto; Ishak Rahman; Aryho Gustira Suprayogi (Jurnal Ekonomi & Bisnis, 2021)
This study aims to determine whether the BPUM program has been right on target or not in accordance with the program socialization and the program objectives have been set. This type of research is qualitative research. The data used is primary data, namely data obtained directly from recipients of BPUM assistance. The data collection technique is by using interviews. Informants in this study consisted of main informants and key informants. The data analysis tool used is by using the theory of Miles and Huberman which consists of data collection, data reduction, data presentation and drawing conclusions. Furthermore, the researcher also conducted the validity of the data by referring to the theory of Miles and Huberman. The results showed that: 1) The distribution of the BPUM program was deemed not right on target, because there were BPUM recipients who did not meet the criteria. 2) The outreach of the program did not run effectively, because the community was still confused about the BPUM program, whether it was related to the correctness of the program, program requirements, and program submissions. 3) The program objectives were not implemented properly, because the program was not well targeted, resulting in the inappropriate use of BPUM funds. in place.